OBJECT-ORIENTED PROGRAMMING IN C++ - LAFORE,ROBERT (South Asia Pearson, 2002)
Begins with the basic principles of the C++ programming language and systematically introduces increasingly advanced topics while illustrating the OOP methodology. This work contains chapters each of which reflects the ANSI C++ standard and the examples mirror the practices and standards.
Keywords: C++; COMPUTER PROGRAMMING